Advertisement text as functional variety of speech (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
In the article the review of different interpretations of advertisement as forms of activity is done and the generalized classification of advertisement reports offers. Advertisement speech as type of mass communication and the model of advertisement communication is described. Communicative-speech descriptions of advertisement text are given and to define the place of texts of advertisement in the system of functional styles was given it a shoot.
Keywords: advertisement; mass communication; advertisement communication; communicative act; advertisement text; informative style; advertisement substyle